Maximal accumulated oxygen deficit is influenced by chronological age and is related to intensity of VO 2PEAK - de Andrade, Vitor Luiz [UNESP]; Kalva-Filho, Carlos Augusto; Campos, Eduardo Zapaterra; Papoti, Marcelo [UNESP] (Springer Nature, 2019)
Purpose: This study aimed to verify the influence of chronological age on maximal accumulated oxygen deficit (MAOD) and the correlations with maximal oxygen uptake (VO 2PEAK ) and intensity (vVO 2PEAK ). Methods: Thirty-one male athletes underwent an incremental exercise test involving 10 submaximal efforts (50–95% of velocity corresponding to VO 2PEAK [vVO 2PEAK ]) and one supramaximal effort at 110% of vVO 2PEAK to determine MAOD. We analyzed a combined group (n = 31) and two groups according to age (G1 = 15.5 ± 0.5; G2 = 36.0 ± 7.9 years). Results: The values of absolute VO 2PEAK (4.3 ± 0.4 L·min −1 ) and vVO 2PEAK (15.9 ± 1.7 km·h −1 ) were higher in G2 than those in G1 (3.5 ± 0.3 L·min −1 ; 14.6 ± 0.9 km·h −1 ). Individuals in G1 had absolute and relative values of MAOD (2.4 ± 0.7 L; 35.1 ± 11.1 mL·kg −1 ) lower than those in G2 (3.9 ± 0.9 L; 46.8 ± 10.9 mL·kg −1 ). Correlations between MAOD and performance during the experimental protocol were tested; VO 2PEAK and vVO 2PEAK yielded correlations with performance (n = 31; r = 0.56; r = 0.60). Moreover, when corrected for chronological age, we detected correlations between absolute and relative values of MAOD and VO 2PEAK (r = 0.42; r = 0.61) and vVO 2PEAK (r = 0.43; r = 0.56). Conclusions: The MAOD is influenced by chronological age and is related to VO 2PEAK and vVO 2PEAK independent of age.
Keywords: Age; Anaerobic; Capacity; Fitness; MAOD; Performance; Sports